1998
DOI: 10.1016/s0014-5793(98)00356-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Kupffer cell inactivator gadolinium chloride on rat liver oxygen uptake and content of mitochondrial cytochromes

Abstract: The effect of gadolinium chloride (GdCl Q ) on the content of rat liver mitochondrial cytochromes was investigated in relation to the basal rate of O P uptake and Kupffer cell functioning, assessed in liver perfusion studies. (1) A single dose of GdCl Q (10 mg/kg) produced a significant diminution in Kupffer cell functioning, evidenced by the decreases in colloidal carbon uptake and in carbon-induced O P uptake observed at 62 4 h after treatment, without changes in the sinusoidal lactate dehydrogenase efflux a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This competition is due to the fact that the cristal radius of gadolinium is similar to that of calcium, while the valency of the former is higher (Klein et al, 1994;Roland et al, 1999). GdCl 3 moderately alters microvascular perfusion in rat liver (Rüttinger et al, 1996) and reversibly decreases O 2 consumption by lowering the levels of mitochondrial cytochromes c 1 and c (Ferreira et al, 1998). Moreover, gadolinium increases the expression of hepatic cytokines and several cytokine-regulated transcription factors, such as c-JUN, C/EBP-b, and C/EBP-d (Decker, 1990;Rai et al, 1996).…”
Section: Toxicological Effects Of Lanthanidesmentioning
confidence: 99%
“…This competition is due to the fact that the cristal radius of gadolinium is similar to that of calcium, while the valency of the former is higher (Klein et al, 1994;Roland et al, 1999). GdCl 3 moderately alters microvascular perfusion in rat liver (Rüttinger et al, 1996) and reversibly decreases O 2 consumption by lowering the levels of mitochondrial cytochromes c 1 and c (Ferreira et al, 1998). Moreover, gadolinium increases the expression of hepatic cytokines and several cytokine-regulated transcription factors, such as c-JUN, C/EBP-b, and C/EBP-d (Decker, 1990;Rai et al, 1996).…”
Section: Toxicological Effects Of Lanthanidesmentioning
confidence: 99%
“…In addition, Shen et al (24) and Fu et al (25) demonstrated that Gd promoted cell proliferation in mouse embryo fibroblast NIH3T3 cells. Ferreira et al (26) indicated that no effect was noted in regards to the viability of Kupffer cells after GdCl 3 exposure. Our data also revealed that there was no viability impact (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a decrease in cell viability, an increase in cell death through apoptosis, and autophagic activation have been associated with Gd (III) toxicity [10,30,34,40,[46][47][48]51,58,60,64,70,99,113]. Mitochondrial dysfunction [38,42,51,91,108,109] and suppressing mitochondria membrane potential [62,101] were also described. Besides cytotoxic, genotoxic potential has also been attributed to Gd (III) exposure [28,45,62], and DNA cleavage of peripheral blood lymphocytes was reported [70,103].…”
Section: Reference Study Design Main Findingsmentioning
confidence: 99%